Alternative Pathways for Hearing Care May Address Disparities in Access - Willink, Amber; Assi, Lama; Nieman, Carrie; McMahon, Catherine; Lin, Frank R.; Reed, Nicholas S. (Frontiers in Digital Health, 2021)
Background/Objectives: Low-uptake of hearing aids among older adults has long dogged the hearing care system in the U.S. and other countries. The introduction of over-the-counter hearing aids is set to disrupt the predominantly high-cost, specialty clinic-based delivery model of hearing care with the hope of increasing accessibility and affordability of hearing care. However, the current model of hearing care delivery may not be reaching everyone with hearing loss who have yet to use hearing aids. In this study, we examine the group of people who do not use hearing aids and describe their characteristics and health care utilization patterns. We also consider what other healthcare pathways may be utilized to increase access to hearing treatment. Design: Cross-sectional, the 2017 Medicare Current Beneficiary Survey. Setting: Non-institutionalized adults enrolled in Medicare, the U.S. public health insurance program for older adults (65 years and older) and those with qualifying medical conditions and disabilities. Participants: A nationally representative sample of 7,361 Medicare beneficiaries with self-reported trouble hearing and/or hearing aid use. Measurements: Survey-weighted proportions described the population characteristics and health care utilization of those with hearing loss by hearing aid use, and the characteristics of those with untreated hearing loss by health care service type utilized. Results: Women, racial/ethnic minorities, and low-income Medicare beneficiaries with self-reported hearing trouble were less likely to report using hearing aids than their peers. Among those who do not use hearing aids, the most commonly used health care services were obtaining prescription drugs (64%) and seeing a medical provider (50%). Only 20% did not access either service in the past year. These individuals were more likely to be young and to have higher educational attainment and income. Conclusion: Alternative models of care delivered through pharmacies and general medical practices may facilitate access to currently underserved populations as they are particularly high touch-points for Medicare beneficiaries with untreated hearing trouble. As care needs will vary across a spectrum of hearing loss, alternative models of hearing care should look to complement not substitute for existing access pathways to hearing care.